Revelando o sentimento de pertença com adolescentes a partir de uma pesquisa participativa - Speranza, Marina (Universidade Federal de São Carlos, 2025)
This decolonial study seeks to break historical silences and question the notion of a universal knowledge. By confronting the coloniality of knowledge, particularly the myth of scientific neutrality, I acknowledge my own non-neutrality and adopt writing in both the first-person singular and plural. The use of the plural expresses the voices of a collective of adolescents who participated in the investigation as researchers, recognizing them as protagonists of their life processes and the topics that concern them. This choice responds to the need to overcome adult-centered and exclusionary perspectives that have historically marked the production of knowledge about this population. Furthermore, despite advances in the field of child and adolescent mental health, there is still a need to expand knowledge production focused on adolescents, in order to support the design and implementation of effective mental health promotion strategies that recognize their singularities, given the increasing experiences of suffering among adolescents. The sense of belonging has been highlighted as an important element in this debate, as it directly influences adolescents’ mental health. Objectives: To explore, identify, and analyse adolescents’ perspectives on the sense of belonging, examining its relationship with the different contexts in which they are embedded and with mental health. Methodology: The theoretical-methodological framework that underpins this investigation is participatory research, characterized by its commitment to occur democratically and horizontally, and to be conducted WITH the subjects rather than ON them, which already implies a potential for transforming reality. The study took place in a community space located in a socially vulnerable territory. Seven adolescents participated, and their engagement was fostered through creative methodologies and methodological coexistence, also supported by my professional perspective as an occupational therapist and by the principles of Popular Health Education. To produce the data, we used various resources, including poster and mural construction, field trips inside and outside the territory, model-making, photography, and interviews, which stimulated group discussions. I also used field diary records written by myself. Data analysis was conducted collectively and integrated into the production process itself. Results: Data were constructed throughout the process and are organized into three axes. In the first, I describe how adolescents’ participation in the research was constituted. As the research group consolidated, the sense of belonging to the collective also strengthened. This belonging, present from the beginning, acted as a driving force for participation: the more it expanded, the more significant adolescents’ engagement in the investigative process became. In the second axis, I present data emerging from the experience of sharing daily life with adolescents, highlighting how they experienced the community space. We observed that the sense of belonging is reinforced when there are opportunities to play, share food, and move freely. In the final axis, I describe activities developed at a stage of the research when adolescents already had a more solid participation repertoire and demonstrated greater proactivity, showing how “belonging-being” (“perten-ser”) enhances participation/action (“particip-ação”). From these activities, we produced data revealing adolescents’ appreciation for experiences of community and solidarity experiences, the complexities and difficulties of social relationships among them, and the school as a space perceived as one of exclusion and non-belonging, while also providing adolescents’ suggestions to transform this school reality. Discussion: Initially, I propose a reflection that highlights the sense of belonging as an analytical key to understanding adolescent participation. Then, I emphasize that “belonging-being” seems to be related to the strengthening of bonds, connecting to concrete possibilities of access and rights guarantees. I also discuss belonging in light of social markers and intersectionalities, emphasizing that “belonging-being” in contexts of social inequality and exposure to different forms of prejudice and violence constitutes an act of resistance. Finally, I address my role as a researcher and occupational therapist, reflecting on the contributions of the field to conducting participatory research.
Revealing the sense of belonging with adolescents through a participatory research approach
Keywords: adolescência; sentimento de pertença; saúde mental; terapia ocupacional; adolescence; sense of belonging; mental health; participatory research; occupacional therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar